2015
DOI: 10.1007/s00464-014-4053-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the major postoperative complications between laparoscopic distal and total gastrectomies for gastric cancer using Clavien–Dindo classification

Abstract: More major complications were observed for LATG, particularly with esophagojejunostomy. These results show that LATG is more invasive than LADG in terms of the postoperative morbidity. More caution and experience are needed when performing LATG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 27 publications
3
32
4
Order By: Relevance
“…There was significant heterogeneity among studies ( p = 0.13; I 2 = 51%), so we used a random-effect model here(Fig 2). Five studies [6,7,13,14,17] reported harvested lymph nodes, meta-analysis confirmed that TG procedure could retrieve more lymph nodes than DG (MD = 4.33, 95% CI = 2.34–6.31, p <0.0001) (Fig 2). …”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…There was significant heterogeneity among studies ( p = 0.13; I 2 = 51%), so we used a random-effect model here(Fig 2). Five studies [6,7,13,14,17] reported harvested lymph nodes, meta-analysis confirmed that TG procedure could retrieve more lymph nodes than DG (MD = 4.33, 95% CI = 2.34–6.31, p <0.0001) (Fig 2). …”
Section: Resultsmentioning
confidence: 79%
“…The flow diagram of reviews shows the detailed process of selection (Fig 1). Finally, 11 studies [6,7,9–17] involving 5447 patients (2418 by TG vs 3029 by DG) were included for our analysis which included Laparoscopy-assisted and open gastrectomy for gastric cancer (Table 3). The baseline characteristics between both groups were shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations